2012
DOI: 10.1111/j.1365-263x.2011.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Bond strength and morphology of resin materials applied to the occlusal surface of primary molars

Abstract: Under the conditions of this study, OptiBond FL was the best material to be used for sealing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 21 publications
4
11
0
Order By: Relevance
“…Primary teeth show morphological as well as histopathological characteristics, and the paradigms on adhesive techniques on permanent teeth cannot simply be transferred to the primary dentition. In terms of primary enamel, the presented research results confirm the convincing adhesive strength of adhesive systems based on phosphoric etching, as known from publications on the primary as well as the permanent dentition [26,27]. However, no significant difference of shear bond strength was determined comparing the experimental groups, except for Prime&Bond NT without phosphoric etching.…”
Section: Discussionsupporting
confidence: 89%
“…Primary teeth show morphological as well as histopathological characteristics, and the paradigms on adhesive techniques on permanent teeth cannot simply be transferred to the primary dentition. In terms of primary enamel, the presented research results confirm the convincing adhesive strength of adhesive systems based on phosphoric etching, as known from publications on the primary as well as the permanent dentition [26,27]. However, no significant difference of shear bond strength was determined comparing the experimental groups, except for Prime&Bond NT without phosphoric etching.…”
Section: Discussionsupporting
confidence: 89%
“…The results showed greater adherence of the OptiBond FL at 24h, compared to Fluroshield, Clinpro TM XT and Vitremer TM , which showed a similar adhesion. This result is consistent with other studies 11,15,33,34 and can be explained by the lower viscosity of the adhesive system, as compared to other materials. OptiBond FL fulfills adequately the micro porosities of enamel produced by acid conditioning 15 , forming extensions of the material (tags) 37 that favored the adhesion.…”
Section: Micro Tensile Strength Testingsupporting
confidence: 93%
“…This result is consistent with other studies 11,15,33,34 and can be explained by the lower viscosity of the adhesive system, as compared to other materials. OptiBond FL fulfills adequately the micro porosities of enamel produced by acid conditioning 15 , forming extensions of the material (tags) 37 that favored the adhesion. On the other hand, the highest viscosity of other materials may have resulted in less wetting of surfaces of the conditioned enamel, limiting the formation of extensions to the interior of the enamel, which can justify the lowest values of adherence among them in 24 hours.…”
Section: Micro Tensile Strength Testingsupporting
confidence: 93%
See 1 more Smart Citation
“…Of the etch-and-rinse adhesive systems used in the present study, Ramires-Romito et al [39] reported higher microtensile bond strength of primary enamel with OptiBond FL than with the self-etch version, OptiBond Solo SE. Lemos et al [40] demonstrated higher bond strength and a better-defined etching pattern and resin tags on primary enamel with OptiBond FL than with OptiBond All-in-One. Despite the results reported for primary enamel, it has been suggested that optimal bonding to primary dentin is achieved with self-etch adhesive systems [4].…”
Section: Discussionmentioning
confidence: 99%